A novel bifunctional thermo-sensitive poly(lactic acid)@poly(butylene succinate) core–shell fibrous separator prepared by a coaxial electrospinning route for safe lithium-ion batteries. Issue 44 (1st November 2017) - Jiang, Xiaoyu; Xiao, Lifen; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract : A thermally induced shutdown separator of PLA@PBS is successfully fabricated by a facile coaxial electrospinning process for safe lithium ion batteries. Abstract : Safety, energy and power density are critical issues for successful application of lithium-ion batteries (LIBs) in portable electronic devices, electric vehicles (EVs) and large-scale energy storage systems. A separator is a key component to ensure the safety and improve the performance of LIBs. Herein, a thermally induced shutdown separator of poly(lactic acid)@poly(butylene succinate) (PLA@PBS) is successfully fabricated by a facile coaxial electrospinning process. The electrospun PLA@PBS separator possesses synchronous characteristics of high thermal sensitivity (prompt shutdown response) and high thermal stability (structural integrity) as well as excellent wettability to liquid electrolytes. Full cells using the bifunctional PLA@PBS separators exhibit superior cycling performance and rate capability compared to those using commercial Celgard separators. These attractive characteristics make the PLA@PBS membrane a promising separator for high safety and high energy/power density LIBs.